2006
DOI: 10.1136/gut.2005.065045
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation in familial pancreatic cancer

Abstract: Background: Previous studies of anticipation in familial pancreatic cancer have been small and subject to ascertainment bias. Our aim was to determine evidence for anticipation in a large number of European families. Patients and methods: A total of 1223 individuals at risk from 106 families (264 affected individuals) were investigated. Generation G3 was defined as the latest generation that included any individual aged over 39 years; preceding generations were then defined as G2 and G1. Results: With 80 affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(59 citation statements)
references
References 47 publications
1
54
1
3
Order By: Relevance
“…The fact that the risk of pancreatic cancer associated with sibling history was higher might indicate a recessive mode of inheritance. The greater risk in siblings than in offspring could also suggest that anticipation is operative in familial pancreatic cancer (Lerch, 2006;McFaul et al, 2006). Previous studies reported an increased risk of pancreatic cancer in the offspring of patients with cancers of the pancreas, rectum and lungs (Hemminki and Li, 2003a).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the risk of pancreatic cancer associated with sibling history was higher might indicate a recessive mode of inheritance. The greater risk in siblings than in offspring could also suggest that anticipation is operative in familial pancreatic cancer (Lerch, 2006;McFaul et al, 2006). Previous studies reported an increased risk of pancreatic cancer in the offspring of patients with cancers of the pancreas, rectum and lungs (Hemminki and Li, 2003a).…”
Section: Discussionmentioning
confidence: 99%
“…Anticipation has been well recognized in a number of disorders including Huntington's disease (Ranen et al, 1995), familial chronic myeloproliferative disorders (Rumi et al, 2007), Lynch syndrome (Nilbert et al, 2009), familial hematologic malignancies (Tegg et al, 2011), and familial pancreatic cancer (McFaul et al, 2006). The underlying mechanisms for anticipation likely differ between different types of disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This risk has been estimated to be 2.3 to 4.5-fold greater in individuals with one FDR with pancreatic cancer, 6.4-fold greater in individuals with two FDRs with the disease and 32 to 57-fold greater in individuals with three or more FDRs affected [29][30][31][32] . Similarly to other familial tumors, the median age of presentation in patients with FPC is up to 20 years earlier than in patients with sporadic cancer (49 years vs 61 years) [33][34][35] with an ''anticipation phenomenon'' in the affected kindred and a trend to become more severe and appear at an earlier age as the disorder is passed from one generation to the next [35,36] . Currently, the genetic etiology of most cases of FPC remains undetermined but complex segregation analysis of these patients has led to the discovery of various candidate pancreatic cancer susceptibility genes such as BRCA2 (6%-17% of cases) [37,38] , partner and localizer of BRCA2 (PALB2) (1%-4% of cases) [39,40] and palladin, even if mutations of the latter have been identified in normal controls as well [41][42][43] .…”
Section: Familial Pancreatic Cancermentioning
confidence: 99%